Three grades of self involvement and the deduction of objectivity in The Practical Self. - Rattan, Gurpreet (Inquiry, 2025)
Does self-consciousness entail objectivity, that the subject of self-consciousness is related to a mind-independent world? Anil Gomes, in his elegant and thought-provoking book, The Practical Self, gives a new and absorbing account - a contemporary "deduction" - of how objectivity follows from self-consciousness. According to Gomes, the self-conscious subject must assent to the claim that she, herself, is the agent of her thinking. Further this assent by the self-conscious subject is sustained by a relation to a community of subjects, also agents, holding one another responsible for their thinking. Gomes's idea is that this relation to others is a relation to a mind-independent world. I do not argue against Gomes, but instead, pushing further in the same direction, argue that the self-conscious subject must also dissent from the claim that she herself is an object. I also ask about how Gomes's deduction amounts to a deduction of objectivity. Here I offer Gomes another way to think about objectivity and how his deduction of a relation between the self-conscious subject and a community of subjects constitutes a deduction of objectivity.